MEDIA EXPOSURE, PERCEPTION, KNOWLEDGE, AND BEHAVIORS IN HEALTH PROTECTION ON PANDEMIC FOR JUNIOR HIGH SCHOOL STUDENTS: CASE OF COVID-19 - Sripairoj, Kanyaphat; Sarayuthpitak, Jintana; Rodpipat, Sarinya (Academic Journal of Thailand National Sports University, 2022)
This research was a cross - sectional analytical study with the objective of studying media exposure, perception, knowledge and behaviors in health protection on the pandemic for junior high school students: case of COVID - 19. The samples were 540 junior high school students from 10 schools in Thailand, obtained by multi -stage sampling. The tool used was online questionnaires. The data were analyzed using Pearson’s Correlation Coefficient statistics. The results of the research were as follows: The samples had media exposure, perception of information, knowledge regarding COVID - 19 and behaviors in health protection on the pandemic of the COVID - 19 ranged from medium to high levels. Social media such as Facebook, Line, Twitter, etc. were the most exposed sources of information. The issues which provide the most perception of information were watching, listening, talking, reading or researching the situation of the COVID - 19 outbreak in Thailand. The subjects which provide the most information were the symptoms and treatments of COVID - 19 and the most appropriate behaviors in health protection during pandemic: Case COVID - 19 was the behavior of wearing mask. Furthermore, it was found that media exposure, perception of information and knowledge regarding COVID - 19 was positively correlated with behaviors in health protection on COVID-19 (r = 0.58, 0.61 and 0.20 respectively). The study result showed that media exposure, perception and knowledge regarding COVID - 19 are factors that affect behaviors in health protection during the pandemic for junior high school students in COVID - 19 situation.